Inspiring Technologies for Digital Inclusivity - Chiew, Kang Leng (Prague University of Economics and Business, 2021)
This editorial aims to summarise the special issue entitled Inspiring Technologies for Digital Inclusivity, which was prepared from selected papers from the 12th International Conference on IT in Asia (CITA'21). The special issue consists of five scientific articles.